Too many murders : a Carmine Delmonico novel - McCullough, Colleen, 1937-2015 (McCullough, Colleen, 1937-2015. Carmine Delmonico novel., 2009)
On a beautiful spring day in the little city of Holloman, Connecticut, home to prestigious Chubb University and armaments giant Cornucopia, chief of detectives Captain Carmine Delmonico has more pressing concerns than finding a name for his infant son: twelve murders have taken place in one day, and Delmonico is drawn into a gruesome web of secrets and lies.